Despacho de caminhões em mineração usando lógica nebulosa, visando ao atendimento simultâneo de políticas excludentes - Eduardo Barbosa Pinto (2008)
This work shows the development of an algorithm to truck dispatch in open pit mines, using fuzzy logic. This algorithm allows achieving the productivity and qualitys polices, that are naturally excluding, in the same time. Virtual mines simulation was used to test the algorithm. The results of simulation showed that the police that use fuzzy logic presents a gain of quality in relation of productivitys police, and a gain of productivity in relation of qualitys police. The results showed also that, among the three dispatch alternative polices (quality, productivity or both criterions), the police proposed in this work is the most generator of concurrent gain of quality and productivity.